Pengembangan Sistem Informasi Distribusi Buku Berbasis Web (Studi Kasus: Penerbit Aryoko Indonesia) - Dimas Hamdhan Prasetyo; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
CV. Aryoko Indonesia is a publisher organization using Aryoko Indonesia Publisher as the brand name. It has two types of resellers: agent based resellers and regular resellers. Resellers order books through a desktop application following by WhatsApp for confirmation. This process takes time and involves manual work which has higher human error risks. In addition to that, the desktop application also has limitations. This study was conducted to design and develop a web-based application that overcomes those problems. To develop the application, this study used Waterfall approach which includes Communication, Planning, Modeling, Construction and Deployment. This study also used Business Process Modelling Notation (BPMN) and Unified Modelling Language (UML) to modelling the data and processes. The application was developed by using framework Laravel and tested with white-box testing and black-box testing.